Minimally Invasive Isolated Tricuspid Valve Repair After Left-Sided Valve Surgery: A Single-Center Experience - Dai, Xiaoyi; Teng, Peng; Miao, Sihan; Zheng, Junnan; Si, Wei; Zheng, Qi; Qin, Ke; Ma, Liang (Frontiers in Surgery, 2022)
Background: Tricuspid regurgitation after left-sided valve surgery was associated with terrible outcomes and high perioperative mortality for redo surgical treatment. In current years, minimally invasive redo isolated tricuspid valve repair is increasingly performed in our institution to address tricuspid regurgitation. Methods: Thirty-seven consecutive patients with previous left-sided valve surgery underwent minimally invasive isolated tricuspid valve repair in our institution between November 2017 and December 2020. Twenty-nine patients(78.4%) were women and the mean age of patients was 58.4±8.5 years. Follow-up was 100% complete with a mean follow-up time of 17.2±9.5 months. Results: Both the in-hospital and 30-day mortalities were 2.7%. The overall NYHA class had improved significantly during the follow-up(p＜0.001). The grade of TR had decreased before discharge(p＜0.001) and during the follow-up(p＜0.001) compared with the preoperative level although severe TR was recurrent in one patient. Conclusions: Minimally invasive isolated tricuspid valve repair has acceptable early and midterm outcomes, may be the preferred surgical option to address tricuspid regurgitation after previous left-sided valve surgery when it is feasible.